Correlation Analysis between Online Interaction and Adolescent Psychological Well-Being - Fernando Setzer; Jailson Baltatu; Rodrigo de Martins; Carlos Versiani (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Social media use among adolescents and young adults has become a phenomenon that significantly affects psychological well-being. This study aimed to analyze social media usage patterns and their relationship with psychological well-being among Brazilian youth aged 15–24 years. This study used a descriptive–correlational quantitative approach with a cross-sectional design, collecting data from 250 respondents through an online survey conducted between August 2024 and August 2025. The instruments used included the Social Media Use Patterns Questionnaire, Satisfaction with Life Scale (SWLS), Perceived Stress Scale (PSS-10), and UCLA Loneliness Scale. The results showed significant variation in social media usage patterns, including daily duration, platform type, and purpose of use. Correlation analysis indicates that intense social media use is positively correlated with stress and loneliness levels, but negatively correlates with life satisfaction. The cluster analysis identified three main groups of users: light, medium, and heavy users, with significant differences in indicators of psychological well-being. Regression analysis shows that the frequency of online social interaction and content consumed is an important predictor of psychological well-being. These findings confirm that understanding social media use patterns is important for mental health interventions and the development of digital literacy strategies among adolescents. Further research is suggested to explore mediator and longitudinal factors related to the impact of social media use on psychological well-being.